From Environment to Body: Microplastics’ Sources, Pathways, and Health Repercussions - Grzelak, Alicja (Journal of Education, Health and Sport, 2024)
Introduction: Microplastics are common pollutants found in the environment and consumer products. People can be exposed to them through eating, breathing, and skin contact. The sources include contaminated food, drinks, seafood, water, salt, and particles in the air, especially in urban and industrial areas. Research suggests these microplastics may cause physical damage, chemical toxicity, inflammation, oxidative stress, and disruption of hormones [1]. Purpose of work: This systematic literature review focuses on providing a comprehensive overview of microplastics in the human body and the health implications due to their presence in human systems [2]. State of knowledge: Research on microplastics has been gaining significant attention among the scientific community. They were found in human stool, blood, and even placental tissue, suggesting they can be absorbed into the human body [3]. Microplastics can enter the body through ingestion, inhalation, and skin contact, and may accumulate in organs over time. Potential adverse health effects include inflammation, immune responses, reproductive toxicity, and translocation to other organs [4][5]. Material and methods: The methodology involved clearly outlining the objectives, a systematic literature search, and a structured process for screening and analyzing studies. The research involved a comprehensive search of scientific databases, including PubMed and Google Scholar. Summary: Microplastics are ubiquitous in the human environment and can enter the body through various exposure pathways. They have the potential to cause a range of adverse health effects, including physical damage, chemical toxicity, inflammation, oxidative stress, and hormonal disruption. However, more research is needed to fully understand the long-term health consequences of microplastics in the human body.